(untitled) (Asian-Australasian Journal of Food Safety and Security, 2022)
Nitrogen (N) fertilization reduces worldwide food insecurity by boosting crop yield and stability. N is one of the most essential macromolecules required for the growth and reproduction of plants. It occurs in diverse chemical forms and circulates in natural and agricultural ecosystems. It is a constituent of chlorophyll, hence is required for the photosynthesis of plants. Plants receive N through their roots in the form of ammonia or nitrate. Nutritional quality and defense of plants that have a direct impact on herbivorous insects are altered by N fertilization and herbivorous insects can differentiate between plants that receive different applications of N fertilizer. Increasing N fertilization has a variable impact on plant species composition, plant growth, plant biomass, and yields. Plant tissue N and protein contents are also affected by nitrogen fertilization. Moreover, nitrogen fertilization affects many aspects of insects such as population dynamics, larval count, larval weight, feeding choice, and oviposition preference. Furthermore, predatory insect abundance, parasitization performance, and development of parasitoids on host insects are negatively affected by N fertilization. Other important effects of N fertilization are the hemolymph protein profile of herbivores, emission of VOCs, phytohormone biosynthesis, and direct and indirect defense of plants. The aim of this literature research is to demonstrate the effects of variable doses of N fertilization on the crop-herbivore-natural enemy tri-trophic systems. The information gathered in this review might help researchers understand the impact of optimal and excessive N fertilization on crop production and food security. Asian Australas. J. Food Saf. Secur. 2022, 6 (2), 48-56